Breaking Bad Patents: Learning from HIV/AIDS to make COVID-19 treatments accessible. Issue 10 (3rd October 2021) - D'Angelo, Alexa B.; Grov, Christian; Johnson, Jeremiah; Freudenberg, Nicholas
ABSTRACT: The COVID-19 pandemic has brought renewed attention to the topic of challenging drug patents in the interest of public health. Pharmaceutical companies have already begun to patent existing medicines for the treatment and prevention of SARS-CoV-2, affording them exclusive manufacturing rights over vital medicines. Advocates have raised concerns regarding the pricing of COVID-19 drugs, as well as patent monopolies on the manufacture of COVID-19 treatments. The HIV/AIDS pandemic provides a useful lens through which we can analyse existing pathways for challenging pharmaceutical patents in the context of global pandemic. In this article, we review three legal pathways for overriding and seizing patents on medicines by describing cases in which they were employed to make antiretroviral drugs more accessible to people living with HIV. Last, we highlight the weaknesses inherent in these pathways and offer advocacy and policy suggestions for how to strengthen these pathways to improve access to COVID-19 treatments as they become available in the United States and globally.